Screening and intervention for intimate partner violence at trauma centers and emergency departments: an evidence-based systematic review from the Eastern Association for the Surgery of Trauma - Hee Soo Jung; Rishi Rattan; Anna Goldenberg; Erin Chang; Stephanie Bonne; D'Andrea Joseph; Amanda L Teichman; Patrick B Murphy; Courtney Edwards; Christina Colosimo; Anna Liveris; Emily Lawson; et al. (Trauma Surgery & Acute Care Open)
Background Intimate partner violence (IPV) is a serious public health issue with a substantial burden on society. Screening and intervention practices vary widely and there are no standard guidelines. Our objective was to review research on current practices for IPV prevention in emergency departments and trauma centers in the USA and provide evidenced-based recommendations.Methods An evidence-based systematic review of the literature was conducted to address screening and intervention for IPV in adult trauma and emergency department patients. The Grading of Recommendations, Assessment, Development and Evaluations methodology was used to determine the quality of evidence. Studies were included if they addressed our prespecified population, intervention, control, and outcomes questions. Case reports, editorials, and abstracts were excluded from review.Results Seven studies met inclusion criteria. All seven were centered around screening for IPV; none addressed interventions when abuse was identified. Screening instruments varied across studies. Although it is unclear if one tool is more accurate than others, significantly more victims were identified when screening protocols were implemented compared with non-standardized approaches to identifying IPV victims.Conclusion Overall, there were very limited data addressing the topic of IPV screening and intervention in emergency medical settings, and the quality of the evidence was low. With likely low risk and a significant potential benefit, we conditionally recommend implementation of a screening protocol to identify victims of IPV in adults treated in the emergency department and trauma centers. Although the purpose of screening would ultimately be to provide resources for victims, no studies that assessed distinct interventions met our inclusion criteria. Therefore, we cannot make specific recommendations related to IPV interventions.PROSPERO registration number CRD42020219517.